Karakterisasi Agronomi 51 Vareitas Unggul Baru Padi (Oryza sativa L.) di Kabupaten Subang - Fitrunnisa, Tiara (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Rice (Oryza sativa L.) is the main commodity as a food ingredient in Indonesia considering that rice is a very valuable commodity. Therefore, it is necessary to create new superior varieties that have high yield characteristics, have high nutritional value, smell good, and are resistant to disease. The varieties that are widely used by farmers include the Ciherang and IR 64 varieties. Characterization is carried out to determine the properties or characters possessed by a plant. Based on the characterization carried out, it can be seen the level of dimilarity between varieties by grouping or clustering which have similarities or differences which can then be used to determine the long distance kinship between rice varieties. This study aims to determine the closest and furthest kinship relationships between 51 new superior varieties of rice (Oryza sativa L.). The research was conducted at the Experimental Garden of the Center for Rice Research (BB Padi), in Sukamandijaya Village, Ciasem District, Subang Regency, West Java. The time for conducting the research is September 2021-March 2022. The method used is descriptive, with 51 treatments, namely new superior varieties, repeated 3 times so there are 153 experimental units. In each observational data the agronomic characters were analyzed by clustering using the UPGMA method. Analysis using NTSYS 2.02i and 2.11 software. The results showed that the grouping results of 51 new high yielding varieties of rice (Oryza sativa L.) formed 14 main groups at a similarity value of 0.75 which showed different traits from each other based on agronomic characteristics of plant height, chilbearing ability, panicle discharge, yellowing of leaves, loss and grain fertility. Based on these results, there are 11 closest kinship relationships and have the farthest kinship in inpari 1 and inpago 8 varieties.